CD2 Immunobiology - Binder, Christian; Cvetkovski, Filip; Sellberg, Felix; Berg, Stefan; Paternina Visbal, Horacio; Sachs, David H.; Berglund, Erik; Berglund, David (Frontiers in Immunology, 2020)
The glycoprotein CD2 is a costimulatory receptor expressed mainly on T and NK cells that binds to LFA3, a cell surface protein expressed on e.g. antigen-presenting cells. CD2 has an important role in the formation and organization of the immunological synapse that is formed between T cells and antigen-presenting cells upon cell-cell conjugation and associated intracellular signaling. CD2 expression is upregulated on memory T cells as well as activated T cells and plays an important role in activation of memory T cells despite the coexistence of several other costimulatory pathways. Anti-CD2 monoclonal antibodies have been shown to induce immune modulatory effects in vitro and clinical studies have proven the safety and efficacy of CD2-targeting biologics. Investigators have highlighted that the lack of attention to the CD2/LFA3 costimulatory pathway is a missed opportunity. Overall, CD2 is an attractive target for monoclonal antibodies intended for treatment of pathologies characterized by undesired T cell activation and offers an avenue to more selectively target memory T cells while favoring immune regulation.